Ellipsometric study of hydrous gold oxide layers and gold surfaces resulting from their electroreduction - Vela, María Elena (1993)
The ellipsometric responses of hydrous gold oxide layers (HAuOLs) and electroreduced gold surfaces (EDAuEs) resulting from HAuOL electroreduction have been studied in the 400–700 nm spectral range. For HAuOL the values of n and k are in the 1.760 ⩽ n ⩽ 1.930 and 0 ⩽ k ⩽ 0.24 ranges respectively. These results are discussed in terms of possible H2O-Au oxide molar ratios. For EDAuEs the values of n(λ) are k(λ) depend on the preparation conditions. These results are interpreted in terms of a composite EDAuE structure consisting of Au domains and solution-filled voids.